Current Potential Antiviral Agents for Coronavirus Disease 2019 (COVID-19) Therapy - Kramy, Prayogi (RSUP Dr. Kariadi, 2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was first discovered in Wuhan, Hubei Province, China. SARS-CoV-2 infects the respiratory tract, which causes coronavirus disease 2019 (COVID-19). Various studies have been conducted to find effective therapies. However, there is still no specific treatment or therapy for COVID-19. This literature review, summarizes some recent research on several potential antiviral agents, both drugs that are commonly used in the medical world such as ivermectin, to medicine from herbal plants and some drugs that are in the process of clinical trials such as remdesivir, lopinavir/ritonavir, Interferon ?, ribavirin, convalescent plasma, and monoclonal antibodies for COVID-19 therapy. KEYWORDS: SARS-CoV-2, COVID-19, Antiviral Agents, Potential therapy.